The relationship between authentic leadership and employee's job performance at Pejabat Pendidikan Daerah (PPD) Bachok, Malaysia / Nadiatul Aina Awang - Awang, Nadiatul Aina (Faculty of Business and Management, 2018)
The purpose of this study is to identify the relationship between authentic leadership and employee's job performance in Pejabat Pendidikan Daerah (PPD) Bachok. The independent variables are self-awareness, balanced processing, relational transparency, and internalized moral perspective while dependent variable is employee's job performance. Besides that, in this research also identify the significant factor of relationship between authentic leadership towards employee's job performance. The questionnaires are divided into several sections and it can be answered by using five-point Likert Scale item which is 1 = Strongly Disagree, 2 = Disagree, 3 = Moderate, 4 = Agree, 5 = Strongly Agree. The respondents for this study were 56 respondents and the researcher get 100 percent of return survey rate. The collected data is analysed by using Statistical Package for the Social Sciences (SPSS) for Window version 23. Based on the result from the analysis of data, there is strong and positive relationship between authentic leadership and employee's job performance in Pejabat Pendidikan Daerah (PPD) Bachok and the most significant variable is self-awareness. Finally, the researcher make conclusion and suggested several recommendations for organization and future research in order to find a better result for this study.